THE STUDY OF STRESS-STRAIN STATE OF CONCRETE BENDING ELEMENT REINFORCED WITH CONVENTIONAL REINFORCEMENT, WITH AMENDMENTS NO. 1 TO SNIP 2.03.01-84* - I. I. Kyrpa; P. O. Pshinko (Nauka ta progres transportu, 2009)
This article presents the results of experimental-and-theoretical research of stressed-and-strained state of flexible ferro-concrete structural member provided with the conventional steel reinforcement and subjected to bending as per Modification № 1 to SNiP (construction regulations) 2.03.01-84*. Concrete and ferro-concrete structural members.